2017
DOI: 10.1186/s13014-017-0842-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing human decisions in IGRT of head-and-neck cancer patients to teach image registration algorithms what experts know

Abstract: BackgroundIn IGRT of deformable head-and-neck anatomy, patient setup corrections are derived by rigid registration methods. In practice, experienced radiation therapists often correct the resulting vectors, thus indicating a different prioritization of alignment of local structures. Purpose of this study is to transfer the knowledge experts apply when correcting the automatically generated result (pre-match) to automated registration.MethodsDatasets of 25 head-and-neck-cancer patients with daily CBCTs and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…6,7 Because of the high sensitivity of proton dose distribution to the patient setup, IGRT setup becomes the ultimate choice to treat each fraction of the treatment plan. 4,[8][9][10] In-room and onboard imaging methods obtain information on target position and movement in intra-and interfractions, compare these images with reference imaging taken initially, and give feedback to optimize patient setup and target localization. Radiation oncology incident learning systems have demonstrated that incorrect or omitted patient shifts during treatment are common near misses or incidents in radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 Because of the high sensitivity of proton dose distribution to the patient setup, IGRT setup becomes the ultimate choice to treat each fraction of the treatment plan. 4,[8][9][10] In-room and onboard imaging methods obtain information on target position and movement in intra-and interfractions, compare these images with reference imaging taken initially, and give feedback to optimize patient setup and target localization. Radiation oncology incident learning systems have demonstrated that incorrect or omitted patient shifts during treatment are common near misses or incidents in radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated the setup accuracy comparison based on cone-beam computed tomography (CBCT) and kilovoltage (kV) images. 10,12,13,[15][16][17] Kraan et al 7 found increased target dose deterioration with increasing setup errors by introducing a systematic shift of isocenter by 2 mm. They also found that the treatment intent of 90% of population to have D98% > 95% of the prescription dose was no longer satisfied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years various advances in image-guided radiotherapy (IGRT) have led to improved precision and accuracy in radiation treatment delivery for head and neck cancer (HNC) [1][2][3]. Three-dimensional image guidance for patient setup allows corrections and could also reduce fail-Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An important task was to undertake a review of the literature to learn from several studies that reported and discussed the rationale for image matching competency training in clinical environments. Several articles reviewed highlighted it is imperative RTs are trained in IGRT, particularly image analysis and decision‐making 7‐12 . An enquiry into the clinical use of IGRT technology and MOSAIQ OIS was important as we needed to understand how we would embed MOSAIQ and actual clinical practice through a range of teaching and learning strategies, whilst understanding the tools which would effectively support teaching.…”
Section: Introductionmentioning
confidence: 99%